1989
DOI: 10.1089/sct.1989.5.13
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Physiological Oxygen Environment on Drug-Induced Cell Lethality of Multicellular Tumor Spheroids from Human Lung Cancer

Abstract: Advanced malignant tumors of certain histological types contain a hypoxic and necrotic core. Multicellular tumor spheroids (MTS) have the characteristics of chronically hypoxic cells in the center. We studied the effects of physiological oxygen environment on MTS growth and the cell lethality produced by doxorubicin (DXR) and cisplatin (DDP). MTS were made from 2 human lung cancer cell lines; PC-6 small cell and PC-10 squamous cell carcinoma, and grown for 2, 3 or 4 weeks; either in 5% CO2/air or 5% 02/5% CO2/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…As we expected, all cancer cells responded to acute hypoxia through the increase of HIF1α protein (Figures 3A-H, 3J). Although these conditions have been widely used in hypoxia studies, some reports suggest that the level of oxygenation may fluctuate and more modest restrictions in oxygen availability may more closely represent actual intratumoral conditions (Inoue and Ohnuma, 1989; Kimura et al, 1996; Cardenas-Navia et al, 2004). A recent report suggested that unlike HIF1α, which is only stabilized under acute hypoxic conditions, HIF2α may accumulate under modest hypoxia or even normal physiological oxygen levels (Holmquist-Mengelbier et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…As we expected, all cancer cells responded to acute hypoxia through the increase of HIF1α protein (Figures 3A-H, 3J). Although these conditions have been widely used in hypoxia studies, some reports suggest that the level of oxygenation may fluctuate and more modest restrictions in oxygen availability may more closely represent actual intratumoral conditions (Inoue and Ohnuma, 1989; Kimura et al, 1996; Cardenas-Navia et al, 2004). A recent report suggested that unlike HIF1α, which is only stabilized under acute hypoxic conditions, HIF2α may accumulate under modest hypoxia or even normal physiological oxygen levels (Holmquist-Mengelbier et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…These methods had many limitations which affected the quality and quantity of the MTS produced. As a consequence of Sutherland' s report that on agar-coated dishes cellcell interaction was enhanced at the expense of cell-dish interactions, the liquid-overlay culture method was developed (Yuhas et a1 1977) and MTS prepared by this method have been used for many studies of the effects of radiation or chemotherapy (Kuroki 1973;Franko & Sutherland 1979;West et a1 1980;Inoue & Ohnuma 1989;Mashiyama et a1 1989;Russell et a1 1989;Schwachoefer et a1 1989;Gaze et a1 1992). Since the development of extracellular matrix analysis of glioma and thyroid cancer cells (Nederman et a1 1984) attempts have been made to increase three-dimensional penetration into the core of MTS and thus enhance the performance of chemotherapy (Sasaki et a1 1984).…”
Section: Discussionmentioning
confidence: 99%